Correction: Zhao, X. et al. Eco-Efficiency of End-of-Pipe Systems: An Extended Environmental Cost Efficiency Framework for Wastewater Treatment. Water 2020, 12, 454 - Xinyue Zhao (Water, 2020)
The authors wish to make the following corrections to this paper [...]